Alliance Instability among Indonesian Subsidiaries in The Nigerian Market - Kurniawan, Harris Turino (Universitas Prasetiya Mulya, 2014)
Alliance instability, which is defined as structural and/or ownership status change in a cooperation, is commonly seen in different partsof the world. This study investigates the main factor causing such phenomenon to occur between Indonesian subsidiaries and their local partners in Nigeria. The findings of the study show that an imbalance of bargaining power becomes a potential factor, which then triggers alliance instability due to conflict of expectations shared between the two sides. The conflict arises because local partners fail to respond to the demands of Indonesian subsidiaries related to the development of distribution systems meant for better dissemination of their products in the country.